Paeonol attenuates retinopathy in streptozotocin-induced diabetes in rats by regulating the oxidative stress and polyol pathway - Kaveri M. Adki; Yogesh A. Kulkarni (Frontiers Media S.A., 2022)
The current research work was planned to study the effects of paeonol in the management of diabetic retinopathy. Diabetes was induced in male Sprague Dawley rats using Streptozotocin (55 mg/kg, i.p.). After 4 weeks, the diabetic animals were treated with paeonol at a dose of 50, 100, and 200 mg/kg body weight daily for the next 4 weeks. At the end of treatment, retinal physiology was studied by recording an electroretinogram (ERG); biochemical parameters and oxidative stress were estimated. The histopathology of the retina was also carried out at the end of the study. The ERG of paeonol-treated animals showed a significant improvement in a-wave amplitude, b-wave amplitude, a-wave latency, and b-wave latency (p < 0.001) at 15 cd s/m2 when compared with the diabetic control animals. The paeonol treatment (200 mg/kg) in diabetic animals showed a significant decrease in the plasma glucose level (p < 0.001) when compared to the animals in diabetic control group. Paeonol also significantly decreased the lactate dehydrogenase, aldose reductase, and sorbitol dehydrogenase levels when compared with the diabetic control animals. The oxidative stress in the eye was significantly reduced after the paeonol treatment in the diabetic rats. The histopathology showed a significant reduction (p < 0.05) in the retinal thickness after the paeonol treatment. The results of the study indicate that paeonol can be considered an effective management option for diabetic retinopathy.